Range of motion predictability after total knee arthroplasty with medial pivot prosthesis() - Carvalho Júnior, Lúcio Honório de (Rev Bras Ortop, 2017)
OBJECTIVE: To assess whether there the final range of motion (ROM) results achieved by patients undergoing total knee arthroplasty (TKA) with prosthesis using Medial Pivot design are predictable. METHODS: Between January and August of 2014, 155 patients with primary osteoarthritis of knee who underwent TKA using the prosthesis ADVANCE(®) Medial Pivot were prospectively assessed. All ROM measures were made and recorded before, during, and after surgery. All patients were clinically assessed preoperatively and postoperatively (15, 45 days, three months, six months, one year, and annually thereafter after surgery); their functional status was assessed using the WOMAC questionnaire. RESULTS: Significant differences (p < 0.001) were observed between the means and medians of ROM in the preoperative when compared with those during the perioperative; the perioperative values, when compared with those after six months postoperative, were also different (p < 0.001). No significant differences were found between the means and medians ROM between the intraoperative period and at the 45-day assessment (ns) and between the means and medians ROM between the preoperative period and at the six-month evaluation (ns). CONCLUSION: The final ROM achieved by patients that underwent TKA with medial pivot prosthesis can be predicted. The perioperative ROM correlates with that at 45 days after surgery. The final ROM is correlated with that of the pre-operative period.